2022
DOI: 10.1007/978-3-030-92790-5_24
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Mapping of Crop Fields with UAV Swarms Based on Information Gain

Abstract: Monitoring crop fields to map features like weeds can be efficiently performed with unmanned aerial vehicles (UAVs) that can cover large areas in a short time due to their privileged perspective and motion speed. However, the need for high-resolution images for precise classification of features (e.g., detecting even the smallest weeds in the field) contrasts with the limited payload and flight time of current UAVs. Thus, it requires several flights to cover a large field uniformly. However, the assumption tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Finally, we aim to use the data gathered from the rover to create a map of the electrostatic environment with an additional focus on electrostatic anomalies or 'hotspots'. This could involve the rover exploring areas based on information gain [23], rather than following a pre-determined path.…”
Section: Rover Trialsmentioning
confidence: 99%
“…Finally, we aim to use the data gathered from the rover to create a map of the electrostatic environment with an additional focus on electrostatic anomalies or 'hotspots'. This could involve the rover exploring areas based on information gain [23], rather than following a pre-determined path.…”
Section: Rover Trialsmentioning
confidence: 99%
“…Unmanned Aerial Vehicles (UAVs) [3] or drones equipped with onboard cameras and sensors have already demonstrated that autonomous flights are possible in real environments. This sparked great interest in a plethora of application scenarios, with crop monitoring [4], surveillance [5], medical and food delivery [6], and search and rescue in disaster areas [7] representing only some of the relevant applications of UAVs.…”
Section: Introductionmentioning
confidence: 99%
“…By modifying plans online, such strategies enable adapting the flight path according to the mission aim to maximize the value of collected data. This can be used for improving the geometric estimation [22] or for semantic estimation tasks [35,5]. Several previous studies in UAV-based informative planning either consider planning at a fixed altitude [37,31], i.e.…”
Section: Introductionmentioning
confidence: 99%